Writing Beyond Pen and Parchment Inscribed Objects in Medieval European Literature - Wagner, Ricarda; Neufeld, Christine; Lieb, Ludger (Materiale Textkulturen, 2019)
In the Middle Ages, writing was not confined to manuscripts, but inscribed in the broader material world, in textiles and tombs, on weapons or human skin. This volume presents the first comparative overview of text-bearing artefacts in medieval German, Old Norse, British, French, Italian and Iberian literature and offers a fresh perspective on the medieval world that takes seriously the vibrancy of matter as a vital aspect of textual culture.